The Impact of Supply Chain Management Practices on the Performance of Private Universities in Malaysia - Basu, Govindaraju; Jeyasingam, John; Habib, Md.Mamun; Letchmana, Uvarani; Radhakrishnan, Ravindran (International Journal of Supply Chain Management, 2017)
Abstract Supply chain management SCM practices have determined the performance of organizations throughout the years.  Recently there has been an upsurge in research on SCM and related practices in the education industry. The objective of this paper is to explore the potential benefits of adopting supply chain management practices towards the achievement of performance and to attain competitiveness in education industry. This empirical study was conducted among the Malaysian private universities. A total of ten universities are selected and 119 responses were received. The research design consisted of a cross sectional study of selected private universities in Malaysia based on their Setara rating as A, B and C categories. Factor analysis was conducted to explain the variance in the observed variables. Multiple regression analysis was used to test the hypotheses. The empirical results showed that the SCM practices have a positive impact on universitperformance especially in the of area information sharing and innovation which showing the highest impact. This study may contribute to a more in-depth analysis of the impact of SCM on the performance of private universities.